# mathlibdocumentation

linear_algebra.direct_sum.tensor_product

# Tensor products of direct sums #

This file shows that taking tensor_products commutes with taking direct_sums in both arguments.

def tensor_product.direct_sum (R : Type u_1) [comm_ring R] (ι₁ : Type u_2) (ι₂ : Type u_3) [decidable_eq ι₁] [decidable_eq ι₂] (M₁ : ι₁ → Type u_4) (M₂ : ι₂ → Type u_5) [Π (i₁ : ι₁), add_comm_group (M₁ i₁)] [Π (i₂ : ι₂), add_comm_group (M₂ i₂)] [Π (i₁ : ι₁), (M₁ i₁)] [Π (i₂ : ι₂), (M₂ i₂)] :
(direct_sum ι₁ (λ (i₁ : ι₁), M₁ i₁)) (direct_sum ι₂ (λ (i₂ : ι₂), M₂ i₂)) ≃ₗ[R] direct_sum (ι₁ × ι₂) (λ (i : ι₁ × ι₂), (M₁ i.fst) (M₂ i.snd))

The linear equivalence (⨁ i₁, M₁ i₁) ⊗ (⨁ i₂, M₂ i₂) ≃ (⨁ i₁, ⨁ i₂, M₁ i₁ ⊗ M₂ i₂), i.e. "tensor product distributes over direct sum".

Equations
@[simp]
theorem tensor_product.direct_sum_lof_tmul_lof (R : Type u_1) [comm_ring R] (ι₁ : Type u_2) (ι₂ : Type u_3) [decidable_eq ι₁] [decidable_eq ι₂] (M₁ : ι₁ → Type u_4) (M₂ : ι₂ → Type u_5) [Π (i₁ : ι₁), add_comm_group (M₁ i₁)] [Π (i₂ : ι₂), add_comm_group (M₂ i₂)] [Π (i₁ : ι₁), (M₁ i₁)] [Π (i₂ : ι₂), (M₂ i₂)] (i₁ : ι₁) (m₁ : M₁ i₁) (i₂ : ι₂) (m₂ : M₂ i₂) :
ι₂ M₁ M₂) ( ι₁ M₁ i₁) m₁ ⊗ₜ[R] ι₂ M₂ i₂) m₂) = (ι₁ × ι₂) (λ (i : ι₁ × ι₂), (M₁ i.fst) (M₂ i.snd)) (i₁, i₂)) (m₁ ⊗ₜ[R] m₂)